2005
DOI: 10.1111/j.1460-9568.2005.03918.x
|View full text |Cite
|
Sign up to set email alerts
|

Both oral and caudal parts of the spinal trigeminal nucleus project to the somatosensory thalamus in the rat

Abstract: Recent evidence has been accumulated that not only spinal trigeminal nucleus caudalis (Sp5C) neurons but also spinal trigeminal nucleus oralis (Sp5O) neurons respond to noxious stimuli. It is unknown, however, whether Sp5O neurons project to supratrigeminal structures implicated in the sensory processing of orofacial nociceptive information. This study used retrograde tracing with Fluorogold in rats to investigate and compare the projections from the Sp5O and Sp5C to two major thalamic nuclei that relay ascend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 72 publications
8
33
2
1
Order By: Relevance
“…These results are also supported by anatomical tract tracing studies which show that small-diameter primary afferents from deep and superficial facial structures synapse in laminae I, II and V of SpVc [Hayashi, 1985] and electrophysiological investigations that report SpVc excitation during deep and superficial orofacial noxious stimulation [Amano et al, 1986;Bolton et al, 2005;Imbe et al, 2001]. It appears that the SpVc plays a multidimensional role in the processing of orofacial pain: SpVc projects directly to the ventroposterior medial thalamic nucleus (VPM), which projects to the primary somatosensory cortex [De Chazeron et al, 2004;Guy et al, 2005], and is thought to process the sensory discriminative aspects of pain. The SpVc also projects to the lateral column of the midbrain periaqueductal gray matter, a region critical for the expression of flight/fight reactions to noxious stimuli [Bandler et al, 2000].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These results are also supported by anatomical tract tracing studies which show that small-diameter primary afferents from deep and superficial facial structures synapse in laminae I, II and V of SpVc [Hayashi, 1985] and electrophysiological investigations that report SpVc excitation during deep and superficial orofacial noxious stimulation [Amano et al, 1986;Bolton et al, 2005;Imbe et al, 2001]. It appears that the SpVc plays a multidimensional role in the processing of orofacial pain: SpVc projects directly to the ventroposterior medial thalamic nucleus (VPM), which projects to the primary somatosensory cortex [De Chazeron et al, 2004;Guy et al, 2005], and is thought to process the sensory discriminative aspects of pain. The SpVc also projects to the lateral column of the midbrain periaqueductal gray matter, a region critical for the expression of flight/fight reactions to noxious stimuli [Bandler et al, 2000].…”
Section: Discussionmentioning
confidence: 61%
“…Unlike SpVc, which receives only direct primary afferent input, it has been reported that SpVo receives both direct primary, and second-order nociceptive inputs from neurons originating in SpVc [Dallel et al, 1998;Greenwood and Sessle, 1976;Hu et al, 1992;Voisin et al, 2002]. Like SpVc, SpVo projects directly to VPM in the thalamus and therefore is likely to play a role in the sensory discriminative aspects of orofacial pain [De Chazeron et al, 2004;Guy et al, 2005].…”
Section: Discussionmentioning
confidence: 97%
“…Neurons of the spinal trigeminal nucleus project caudally to mid and lower cervical motor neurons innervating neck muscles (Devoize et al, 2010), and, in cats, projections have been traced caudally as far as the T6 segment (Matsushita et al, 1981). Rostrally, the spinal trigeminal nucleus projects to the thalamus (Guy et al, 2005), the superior colliculus, and the cerebellum via the inferior olive (Huerta et al, 1983;Xue et al, 2008). This organization supports the TSNC as a key structure in a large neural network modulating activity in motoneurons supplying muscles of the neck and face, and, therefore, should be considered in network models for dystonia.…”
Section: Central Projections Of the Tsncmentioning
confidence: 99%
“…From the neurons in the caudal trigeminal nucleus, pain impulses are projected to the thalamus via the spinothalamic system (Guy et al, 2005). Possibly indicating a role for PDE8 in trigeminal cAMP signaling, the present study shows PDE8A immunoreactivity in the dura, the neurons of the trigeminal ganglion and the caudal trigeminal nucleus.…”
Section: Pde8a and Potential Involvement In Pain Signalingmentioning
confidence: 91%